Consilierea psihologică în gestionarea emoţiilor în faţa incertitudinii [Articol] - Corcevoi, Maria (USARB, 2024)
Managing emotions in the face of uncertainty is a crucial yet challenging process essential for emotional well-being. This article outlines eight practical strategies to navigate uncertainty effectively: accepting the present moment, adopting a growth mindset, clarifying fears, distinguishing between what can and cannot be controlled, creating flexible action plans, letting go of external worries, drawing confidence from past experiences, and aligning life choices with one’s tolerance for uncertainty. Each strategy emphasizes actionable steps, self-reflection, and adaptability, offering a structured framework to transform uncertainty from a source of anxiety into an opportunity for learning and personal growth. With consistent application, these approaches help individuals build emotional resilience and navigate the unknown with greater confidence and clarity.
Keywords: emotional management; uncertainty; growth mindset; emotional resilience; anxiety reduction; tolerance for uncertainty